High-temperature-resistant anti-corrosion high-frequency low-dielectric magnesium oxide-based ceramic material and preparation method thereof
Through the combination of high-energy ball milling method and three-stage sintering process, high-temperature corrosion-resistant high-frequency low-intermediate magnesium oxide-based ceramic materials were prepared, which solved the problem of performance deterioration of existing materials in high-temperature corrosion environments and achieved extreme environments stable work.
Patent Information
- Application Number
- CN202411711510.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-18
AI Technical Summary
Existing microwave dielectric materials are difficult to meet the requirements of corrosion resistance, dielectric properties and mechanical properties in high-temperature corrosion environments, resulting in failure in applications in aerospace, nuclear power and radar systems.
High-temperature and corrosion-resistant high-frequency low-intermediate magnesium oxide-based ceramic materials are prepared by combining high-energy ball milling method with three-stage sintering process. By introducing specific dopants and sintering process optimization, the density and electrical properties of the ceramic are improved.
It achieves stable dielectric and mechanical properties under high-temperature corrosion environments, ensuring the reliability and long life of ceramic materials in aerospace, nuclear power and radar systems.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional ceramic materials, and in particular to a high-temperature resistant, corrosion-resistant, high-frequency, low-dielectric magnesium oxide-based ceramic material and a preparation method thereof. Background Art
[0002] Microwave dielectric ceramics have always been a research hotspot in the field of materials at home and abroad. With the development requirements of aerospace technology, military equipment, energy and chemical industry, nuclear power technology and other fields, especially those used in harsh environments such as high temperature and high corrosion, high-frequency low-dielectric microwave dielectric ceramic materials and microwave devices with high temperature resistance and corrosion resistance have been proposed to have higher performance, higher operating temperature, and both anti-corrosion and dielectric properties and meet the requirements of high-frequency applications. At present, in radar systems, microwave dielectric ceramic devices are required to maintain the stability of signal transmission under high temperature and severe weather conditions to ensure the normal operation of radar systems. In the field of satellite communications and navigation, microwave dielectric ceramic devices also play an important role. Satellites face extreme temperature changes and radiation corrosion in the space environment, requiring microwave dielectric ceramics to have high temperature stability and excellent corrosion resistance. In addition, the requirements for microwave dielectric materials in the aerospace field are extremely strict. Not only are the materials required to be lightweight and high-strength, but they are also required to maintain stable performance under extreme environments such as high temperature, high pressure, and corrosion.
[0003] Existing microwave dielectric materials are difficult to simultaneously meet the requirements for use under the above-mentioned harsh working conditions. The main reason is that the ceramic system used has poor corrosion resistance at high temperatures, which leads to a sharp deterioration of the dielectric and mechanical properties of the material in a high-temperature corrosion environment, thereby causing failure of the radar system or failure of key parts such as aircraft engines.
[0004] Therefore, developing a high temperature resistant, corrosion resistant, high frequency, low dielectric ceramic material and its preparation method has become an urgent problem to be solved. Summary of the invention
[0005] In view of this, the present invention provides a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material and a preparation method thereof, in order to solve the technical problem that the performance of microwave dielectric ceramic materials cannot meet the working conditions under high temperature corrosion and harsh working conditions in the current aerospace, nuclear power, radar systems and other fields.
[0006] On the one hand, the present invention provides a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide based ceramic material, comprising, by mole composition: 90-95 parts of MgO, dopant: Al(NO 3 ) 3 9H 2 O 0.5-1.5 parts, Sm 2 O 3 / Ca(NO 3 ) 29H 2 O 0.5-1.5 parts, MgF 2 / CaF 2 0.05-1.5 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.5-1.0 copies, WO 3 0.01-0.05 parts, BeO 0.01-0.05 parts, LiNO 3 0.01-0.05 parts, NaOH / KOH 0.01-0.05 parts, Mn(C 2 H 3 O 2 )·4H 2 O 0.01-0.05 parts, Fe(NO 3 ) 3 9H 2 O 0.01-0.05 parts, and / or ZrO 2 0-0.05 parts, TiO 2 0-0.05 parts, Cr(NO 3 ) 3 9H 2 O is 0-0.05 parts, Gd 2 O 3 0-0.05 parts, Nb 2 O 5 0-0.05 parts, Ta 2 O 5 One or more of 0-0.05 parts.
[0007] Preferably, the Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 Sm in O 2 O 3 with Ca(NO 3 ) 2 9H 2 The molar ratio of O is 1:2, MgF 2 / CaF 2 MgF 2 With CaF 2 The molar ratio is 1:1, nano-SiO 2 / Si(OC 2 H 5 ) 4 Medium nano-SiO 2 With Si(OC 2 H 5 )4 The molar ratio of NaOH to KOH in NaOH / KOH is 3:1.
[0008] In a second aspect, the present invention also provides a method for preparing the high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material, comprising:
[0009] Step 1: Add dopant: Al(NO 3 ) 3 9H 2 O 0.5-1.5 parts, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O 0.5-1.5 parts, MgF 2 / CaF 2 0.05-1.5 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.5-1.0 copies, WO 3 0.01-0.05 parts, BeO 0.01-0.05 parts, LiNO 3 0.01-0.05 parts, NaOH / KOH 0.01-0.05 parts, Mn(C 2 H 3 O 2 )·4H 2 O0.01-0.05 parts, Fe(NO 3 ) 3 9H 2 O 0.01-0.05 parts, and / or ZrO 2 0-0.05 parts, TiO 2 0-0.05 parts, Cr(NO 3 ) 3 9H 2 O is 0-0.05 parts, Gd 2 O 3 0-0.05 parts, Nb 2 O 5 0-0.05 parts, Ta 2 O 5 Mix one or more of 0-0.05 parts, and perform high-energy ball milling on the dopant once by high-energy ball milling process;
[0010] Step 2: Adding MgO main powder to the dopant after the first high-energy ball milling to perform a second high-energy ball milling to obtain a second ball milled material;
[0011] Step 3: vacuum freeze drying the material after the secondary ball milling to obtain a dried powder;
[0012] Step 4: pre-calcining the dried powder to obtain pre-calcined powder;
[0013] Step 5: Add PVA to the pre-calcined powder, perform granulation and tableting, and obtain a formed sheet product;
[0014] Step 6: Sinter the formed sheet product using a three-stage sintering method and then naturally cool it to room temperature to form porcelain.
[0015] Preferably, the high energy ball milling in step 1 is performed at a speed of 5000-6000 rpm and for a time of 0.5-2.0 h.
[0016] Preferably, the secondary high-energy ball milling in step 2 is performed at a speed of 5000-6000 rpm and for a time of 2.0-3.5 h.
[0017] Preferably, the grinding balls used in the primary high-energy ball milling and the secondary high-energy ball milling are agate balls, and the grinding medium is a mixture of anhydrous ethanol, butanol and deionized water, wherein the volume ratio of anhydrous ethanol, butanol and deionized water is 1:1:2;
[0018] The mass ratio of the reaction material: grinding ball: grinding medium in the primary high-energy ball milling and the secondary high-energy ball milling is 1:1.5-2.5:0.8-1.2;
[0019] In the first high-energy ball milling and the second high-energy ball milling, N-methylpyrrolidone is used as a dispersant.
[0020] Preferably, the pre-firing temperature in step 4 is 700-880°C.
[0021] Preferably, in step 5, the amount of PVA added is 3% to 10%, and the mass fraction of PVA is 1.5% to 5%.
[0022] Preferably, the three-stage sintering in step 6 includes: the sintering temperature in the first stage is 1150-1230°C, and the holding time is 20-40min; the sintering temperature in the second stage is 1460-1530°C, and the holding time is 30-50min; the sintering temperature in the third stage is 1680-1725°C, and the holding time is 120min-150min.
[0023] The present invention provides a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material and a preparation method thereof, wherein the high temperature resistant, corrosion resistant, high frequency, low dielectric ceramic material is prepared by combining a high energy ball milling method with a three-stage sintering process. The high temperature corrosion resistant, high frequency, low dielectric ceramic powder material prepared by the present invention has uniform particle size, high sintering activity, and a dense ceramic structure after sintering, and can achieve stable operation under high temperature corrosion harsh environment conditions. The high frequency, low dielectric ceramic material has broad development space in many fields such as aerospace technology, military equipment, energy chemical industry, and nuclear power technology.
[0024] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. DETAILED DESCRIPTION
[0025] The present invention is further explained below in conjunction with specific implementation schemes, but it is not intended to limit the protection scope of the present invention.
[0026] In order to solve the key technical problem that the performance of microwave dielectric ceramic materials cannot meet the working conditions under high temperature corrosion in the fields of aerospace, nuclear power, radar systems, etc. Firstly, the present invention provides a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material, which comprises, by mole composition: MgO 90-95 parts, Al(NO 3 ) 3 9H 2 O0.5-1.5 parts, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O 0.5-1.5 parts, MgF 2 / CaF 2 0.05-1.5 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.5-1.0 copies, WO 3 0.01-0.05 parts, BeO 0.01-0.05 parts, LiNO 3 0.01-0.05 parts, NaOH / KOH 0.01-0.05 parts, Mn(C 2 H 3 O 2 )·4H 2 O 0.01-0.05 parts, Fe(NO 3 ) 3 9H 2 O0.01-0.05 parts, and / or ZrO 2 0-0.05 parts, TiO2 0-0.05 parts, Cr(NO 3 ) 3 9H 2 O is 0-0.05 parts, Gd 2 O 3 0-0.05 parts, Nb 2 O 5 0-0.05 parts, Ta 2 O 5 One or more of 0-0.05 parts.
[0027] Among them, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 Sm in O 2 O 3 with Ca(NO 3 ) 2 9H 2 The molar ratio of O is 1:2, MgF 2 / CaF 2 MgF 2 With CaF 2 The molar ratio is 1:1, nano-SiO 2 / Si(OC 2 H 5 ) 4 Medium nano-SiO 2 With Si(OC 2 H 5 ) 4 The molar ratio of NaOH to KOH in NaOH / KOH is 1:1;
[0028] The above components are prepared by a method combining a high-energy ball milling method with a three-stage sintering process to prepare a high-temperature resistant, corrosion-resistant, high-frequency, low-dielectric magnesium oxide-based ceramic material.
[0029] The MgO-based ceramic material obtained by combining high-energy ball milling with a three-stage sintering process is the main body of the final high-temperature resistant, corrosion-resistant, high-frequency, low-dielectric ceramic structure. The selected dopants are mostly introduced in the form of ions for doping modification to improve the mixing uniformity of the dopant and the main material, and further improve the mechanical and electrical properties of the ceramic body after subsequent ceramic sintering.
[0030] Among the above components, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O, Nano-SiO 2 / Si(OC 2 H5 ) 4 It mainly plays the role of refining crystals, inhibiting grain growth, improving ceramic corrosion resistance, improving and optimizing ceramic dielectric properties and improving mechanical properties; MgF 2 / CaF 2 、LiNO 3 The introduction of NaOH / KOH can synergistically activate the MgO lattice, inhibit abnormal grain growth and prevent the deterioration of mechanical properties such as ceramic flexural strength; WO 3 、BeO、Mn(C 2 H 3 O 2 )·4H 2 O, Fe(NO 3 ) 3 9H 2 The introduction of O can synergistically improve the quality factor of the material; at the same time, Ca(NO 3 ) 2 9H 2 O、Al(NO 3 ) 3 9H 2 O, Nano-SiO 2 / Si(OC 2 H 5 ) 4 It can form a glass phase with KOH / NaOH, which plays a certain role in reducing the sintering temperature of magnesium oxide-based ceramics. Due to the existence of the glass phase, the flow mass transfer is faster than the general solid phase diffusion mass transfer, thus accelerating the material transfer process, moving to the surface under the action of vapor pressure, filling the pores generated by the volatilization of nitrate substances introduced in the components during the heating process, and also enriching and filling in the grain boundaries of magnesium oxide ceramics in trace amounts, which has a certain pinning effect. In this process, there is also a chemical reaction at the solid-liquid interface, which further accelerates the mass transfer of the entire system, thereby effectively reducing the sintering temperature of the ceramic body and improving the density, dielectric stability and excellent quality factor of the ceramic body, and also has a good moisture-proof and anti-corrosion effect.
[0031] Secondly, the present invention also provides a method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material, comprising:
[0032] 1) Weigh the following components in molar ratio with the weighing accuracy within ±0.0001g. 3 ) 3 9H 2 O0.5-1.5 parts, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O 0.5-1.5 parts, MgF2 / CaF 2 0.05-1.5 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.5-1.0 copies, WO 3 0.01-0.05 parts, BeO 0.01-0.05 parts, LiNO 3 0.01-0.05 parts, NaOH / KOH 0.01-0.05 parts, Mn(C 2 H 3 O 2 )·4H 2 O 0.01-0.05 parts, Fe(NO 3 ) 3 9H 2 O0.01-0.05 parts, and / or ZrO 2 0-0.05 parts, TiO 2 0-0.05 parts, Cr(NO 3 ) 3 9H 2 O is 0-0.05 parts, Gd 2 O 3 0-0.05 parts, Nb 2 O 5 0-0.05 parts, Ta 2 O 5 A mixture of one or more of 0-0.05 parts;
[0033] After mixing, high-energy ball milling is performed once, the ball milling speed is controlled between 5000-6000 rpm, and the high-energy ball milling time is controlled between 0.5-2.0h.
[0034] At this time, the main powder of magnesium oxide is added to the high-energy ball mill hopper for secondary high-energy ball milling. The ball milling speed is controlled between 5000-6000 rpm and the high-energy ball milling time is controlled between 2.0-3.5h. The grinding balls used in the ball mill are agate balls, the grinding media are a mixture of anhydrous ethanol, butanol and deionized water (volume ratio is 1:1:2), N-methylpyrrolidone is used as a dispersant, and the ratio of material: ball: grinding media is 1:1.5~2.5:0.8~1.2.
[0035] 2) The ball-milled material is dried using a vacuum freeze-drying process.
[0036] 3) After drying, the powder is pre-sintered at 700-880°C.
[0037] 4) After grinding, 3% to 10% by mass of PVA (1.5% to 5%) is added to the powder, followed by granulation and tableting.
[0038] 5) The pressed discs are sintered into porcelain using a three-stage sintering process. The first stage is carried out at 1150-1230°C, and the holding time in this stage is 20-40 minutes. At this time, the influence of the additives may be most obvious, and the density changes the most with the firing temperature; the second stage is carried out at 1460-1530°C, and the holding time is 30-50 minutes. At this time, the porcelain body is further densified; the third stage is carried out at 1680-1725°C, and the holding time is controlled at 120-150 minutes, and then naturally cooled to room temperature. At this time, the porcelain body is the densest, the grain boundary is formed, and the glassy material will be enriched at the grain boundary, which improves the density, dielectric stability and excellent quality factor of the porcelain body, and also has good moisture-proof and anti-corrosion effects.
[0039] 6) The surface electrode of the sintered ceramic piece is coated by screen printing technology for electrical performance testing.
[0040] The present invention adopts a method combining high-energy ball milling with a three-stage sintering process to prepare MgO-based ceramic materials. The selected dopants are mostly introduced in the form of ions for doping modification, thereby improving the mixing uniformity of the dopants and the main material, and further improving the mechanical properties and electrical properties of the ceramic body after subsequent ceramic sintering.
[0041] The present invention is further explained below in conjunction with specific embodiments.
[0042] Example 1
[0043] The molar composition is: MgO 95 parts, Al(NO 3 ) 3 9H 2 O1.5 parts, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O 0.5 parts, MgF 2 / CaF 2 0.06 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.8 copies, WO 3 0.01 parts, BeO 0.01 parts, LiNO 3 0.01 parts, NaOH / KOH 0.02 parts, Mn(C 2 H 3 O 2 )·4H 2O0.02 parts, Fe(NO 3 ) 3 9H 2 O0.02 parts, Cr(NO 3 ) 3 9H 2 O 0.01 part, Gd 2 O 3 0.02 parts, Ta 2 O 5 0.01 parts, of which Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 Sm in O 2 O 3 with Ca(NO 3 ) 2 9H 2 The molar ratio of O is 1:2, MgF 2 / CaF 2 MgF 2 With CaF 2 The molar ratio is 1:1, nano-SiO 2 / Si(OC 2 H 5 ) 4 Medium nano-SiO 2 With Si(OC 2 H 5 ) 4 The molar ratio of NaOH to KOH in NaOH / KOH is 3:1.
[0044] The above components were weighed in molar ratio, and the weighing accuracy was controlled within ±0.0001g. The Al(NO 3 ) 3 9H 2 O、Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O、MgF 2 / CaF 2 、Nano-SiO 2 / Si(OC 2 H 5 ) 4 , WO 3 、BeO、LiNO 3 、NaOH / KOH、Mn(C 2 H 3 O 2 )·4H2 O, Fe(NO 3 ) 3 9H 2 O、Cr(NO 3 ) 3 9H 2 O, Gd 2 O 3 、 2 O 5 A variety of dopants were subjected to a high-energy ball milling, the ball milling speed was controlled between 5600 rpm, and the high-energy ball milling time was controlled within 0.5h. Then the magnesium oxide main body powder was added to the high-energy ball mill hopper for a second high-energy ball milling, the ball milling speed was controlled between 6000 rpm, and the high-energy ball milling time was controlled within 2.5h. The grinding balls used in the ball milling were agate balls, the grinding media were a mixture of anhydrous ethanol, butanol and deionized water (ratio of 1:1:2), N-methylpyrrolidone was used as a dispersant, and the material: ball: grinding medium ratio was 1:2:1.
[0045] The ball-milled material is dried using a vacuum freeze-drying process.
[0046] After drying, the powder is pre-sintered at 780°C. After grinding, 5% PVA (2.5% by mass) is added to the powder, followed by granulation and tableting. The pressed discs are sintered into porcelain using a three-stage sintering process. The first stage is carried out at 1180°C, and the heat preservation time is 20 minutes; the second stage is carried out at 1490°C, and the heat preservation time is 40 minutes; the third stage is carried out at 1700°C, and the heat preservation time is controlled at 120 minutes, and then naturally cooled to room temperature.
[0047] The surface electrode coating of the sintered ceramic piece was carried out by screen printing process for electrical performance test. At room temperature 1GHZ, the dielectric constant is 8.5, the quality factor is 68970, and the frequency temperature coefficient is -45ppm; at 1350℃1GHZ, the dielectric constant is 9.2, the quality factor is 63574, and the frequency temperature coefficient is -52ppm; the water resistance stability of the ceramic body was tested, which was Grade I; the alkali corrosion resistance of the ceramic body was tested at 85℃, 0.5ppm / cm 2 .
[0048] Example 2
[0049] The molar composition is: MgO 92 parts, Al(NO 3 ) 3 9H 2 O 1.8 parts, Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 O 0.6 parts, MgF2 / CaF 2 0.07 parts, nano-SiO 2 / Si(OC 2 H 5 ) 4 0.9 copies, WO 3 0.01 parts, BeO 0.02 parts, LiNO 3 0.02 parts, NaOH / KOH 0.03 parts, Mn(C 2 H 3 O 2 )·4H 2 O 0.04 parts, Fe(NO 3 ) 3 9H 2 O 0.05 parts, Cr(NO 3 ) 3 9H 2 O 0.02 parts, Nb 2 O 5 0.02 parts, ZrO 2 0.02 parts, Ta 2 O 5 0.02 parts, of which Sm 2 O 3 / Ca(NO 3 ) 2 9H 2 Sm in O 2 O 3 with Ca(NO 3 ) 2 9H 2 The molar ratio of O is 1:2, MgF 2 / CaF 2 MgF 2 With CaF 2 The molar ratio is 1:1, nano-SiO 2 / Si(OC 2 H 5 ) 4 Medium nano-SiO 2 With Si(OC 2 H 5 ) 4 The molar ratio of NaOH to KOH is 3:1, and the molar ratio of NaOH to KOH in NaOH / KOH is 1:1. The above components are weighed according to the molar ratio, and the weighing accuracy is controlled within ±0.0001g.
[0050] The Al(NO 3 ) 3 9H 2 O、Sm 2 O3 / Ca(NO 3 ) 2 9H 2 O、MgF 2 / CaF 2 、Nano-SiO 2 / Si(OC 2 H 5 ) 4 , WO 3 、BeO、LiNO 3 、NaOH / KOH、Mn(C 2 H 3 O 2 )·4H 2 O, Fe(NO 3 ) 3 9H 2 O、Cr(NO 3 ) 3 9H 2 O、Nb 2 O 5 、ZrO 2 、 2 O 5 A variety of dopants are subjected to a high-energy ball milling, the ball milling speed is controlled between 6000 rpm, and the high-energy ball milling time is controlled within 0.5h. At this time, the main magnesium oxide powder is added to the high-energy ball mill hopper for a second high-energy ball milling, the ball milling speed is controlled between 6000 rpm, and the high-energy ball milling time is controlled within 3.0h. The grinding balls used in the ball milling are agate balls, and the grinding media are a mixture of anhydrous ethanol, butanol and deionized water (ratio of 1:1:2), N-methylpyrrolidone is used as a dispersant, and the ratio of material: ball: grinding medium is 1:2.5:1.2.
[0051] The ball-milled material is dried using a vacuum freeze-drying process.
[0052] After drying, the powder was pre-calcined at 760° C. After grinding, 4.5% by mass fraction (3.5% PVA) was added to the powder, and then granulated and tableted.
[0053] The pressed discs are sintered into porcelain using a three-stage sintering process. The first stage is carried out at 1160°C, with a holding time of 20 minutes; the second stage is carried out at 1480°C, with a holding time of 50 minutes; the third stage is carried out at 1690°C, with a holding time of 120 minutes, and then naturally cooled to room temperature.
[0054] The surface electrode coating of the sintered ceramic piece was carried out by screen printing process for electrical performance test. At room temperature 1GHZ, the dielectric constant is 6.8, the quality factor is 72850, and the frequency temperature coefficient is -25ppm; at 1350℃1GHZ, the dielectric constant is 7.5, the quality factor is 68574, and the frequency temperature coefficient is -33ppm; the water resistance stability of the ceramic body was tested, which was Grade I; the alkali corrosion resistance of the ceramic body was tested at 85℃, 0.6ppm / cm 2 .
[0055] The present invention adopts a method combining high-energy ball milling with a three-stage sintering process to prepare a high-temperature resistant, corrosion-resistant, high-frequency, low-dielectric ceramic material. The high-temperature, corrosion-resistant, high-frequency, low-dielectric ceramic powder material prepared by the present invention has uniform particle size, high sintering activity, and a dense ceramic structure after sintering, and can achieve stable operation under high-temperature corrosion harsh environment conditions. The high-frequency, low-dielectric ceramic material has broad development space in many fields such as aerospace technology, military equipment, energy and chemical industry, and nuclear power technology.
[0056] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0057] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide based ceramic material, characterized in that: The composition comprises, by mole, 90-95 parts of MgO, doping agents: 0.5-1.5 parts of Al(NO3)3·9H2O, 0.5-1.5 parts of Sm2O3 / Ca(NO3)2·9H2O, 0.05-1.5 parts of MgF2 / CaF2, 0.5-1.0 parts of nano-SiO2 / Si(OC2H5)4, 0.01-0.05 parts of WO3, 0.01-0.05 parts of BeO, 0.01-0.05 parts of LiNO3, 0.01-0.05 parts of NaOH / KOH, 0.01-0.05 parts of Mn(C2H3O2)·4H2O, 0.01-0.05 parts of Fe(NO3)3·9H2O 0.01-0.05 parts, and / or one or more of ZrO2 0-0.05 parts, TiO2 0-0.05 parts, Cr(NO3)3·9H2O 0-0.05 parts, Gd2O3 0-0.05 parts, Nb2O5 0-0.05 parts, and Ta2O5 0-0.05 parts.
2. The high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 1, characterized in that: The molar ratio of Sm2O3 to Ca(NO3)2·9H2O in the Sm2O3 / Ca(NO3)2·9H2O is 1:2, the molar ratio of MgF2 to CaF2 in MgF2 / CaF2 is 1:1, the molar ratio of nano-SiO2 to Si(OC2H5)4 in nano-SiO2 / Si(OC2H5)4 is 3:1, and the molar ratio of NaOH to KOH in NaOH / KOH is 1:
1.
3. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric constant magnesium oxide-based ceramic material according to any one of claims 1-2, characterized in that: include: Step 1: Add doping agents: Al(NO3)3·9H2O 0.5-1.5 parts, Sm2O3 / Ca(NO3)2·9H2O 0.5-1.5 parts, MgF2 / CaF2 0.05-1.5 parts, nano-SiO2 / Si(OC2H5)4 0.5-1.0 parts, WO3 0.01-0.05 parts, BeO 0.01-0.05 parts, LiNO3 0.01-0.05 parts, NaOH / KOH 0.01-0.05 parts, Mn(C2H3O2)·4H2O 0.01-0.05 parts, Fe(NO3)3·9H2O 0.01-0.05 parts, and / or 0-0.05 parts of ZrO2, 0-0.05 parts of TiO2, 0-0.05 parts of Cr(NO3)3·9H2O, 0-0.05 parts of Gd2O3, 0-0.05 parts of Nb2O5, 0-0.05 parts of Ta2O5 or more thereof, and high-energy ball milling the dopant once using a high-energy ball milling process; Step 2: adding MgO main powder to the dopant after the first high-energy ball milling to perform a second high-energy ball milling to obtain a second ball milled material; Step 3: vacuum freeze drying the material after the secondary ball milling to obtain a dried powder; Step 4: pre-calcining the dried powder to obtain pre-calcined powder; Step 5: Add PVA to the pre-calcined powder, perform granulation and tableting, and obtain a formed sheet product; Step 6: Sinter the formed sheet product using a three-stage sintering method and then naturally cool it to room temperature to form porcelain.
4. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: The rotation speed of the high energy ball milling in step 1 is 5000-6000 rpm, and the time is 0.5-2.0h.
5. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: The rotation speed of the secondary high-energy ball milling in step 2 is 5000-6000 rpm, and the time is 2.0-3.5h.
6. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: The grinding balls used in the primary high-energy ball milling and the secondary high-energy ball milling are agate balls, and the grinding medium is a mixture of anhydrous ethanol, butanol and deionized water, wherein the volume ratio of anhydrous ethanol, butanol and deionized water is 1:1:2; The mass ratio of the reaction material: grinding ball: grinding medium in the primary high-energy ball milling and the secondary high-energy ball milling is 1:1.5-2.5:0.8-1.2; In the first high-energy ball milling and the second high-energy ball milling, N-methylpyrrolidone is used as a dispersant.
7. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: The pre-firing temperature in step 4 is 700-880°C.
8. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: In step 5, the amount of PVA added is 3% to 10%, and the mass fraction of PVA is 1.5% to 5%.
9. The method for preparing a high temperature resistant, corrosion resistant, high frequency, low dielectric magnesium oxide-based ceramic material according to claim 3, characterized in that: The three-stage sintering in step 6 includes: the sintering temperature of the first stage is 1150-1230°C, and the holding time is 20-40 minutes; the sintering temperature of the second stage is 1460-1530°C, and the holding time is 30-50 minutes; the sintering temperature of the third stage is 1680-1725°C, and the holding time is 120 minutes-150 minutes.